Prankster - Cawthon, Scott, 1971-; Cooper, Elley; Waggener, Andrea Rains, 1960- (Cawthon, Scott, 1971- Five nights at Freddy's. Fazbear frights, 2021)
Presents three novella-length tales of horror set in the world of Five nights at Freddy's.